ANALISIS SISTEM AKUNTANSI PEMBERIAN KREDIT AGUNAN RUMAH (KAR) PADA PT. BANK TABUNGAN NEGARA KANTOR CABANG MANADO - Piay, Yeremia Stevanus Elim; Elim, Inggriani; Lambey, Robert (Universitas Sam Ratulangi, 2018)
Home mortgage loan is a credit facility from PT. Bank Tabungan Negara Branch Office Manado that can be used for various consumer needs by pledging the residence / apartment / shop / house. Implementation Granting of mortgage loans PT. Bank Tabungan Negara Branch Office Manado can be said easy and fast because it uses a good system. The credit accounting system is required to describe the system and procedures for crediting, and how the implementation of internal control over lending. The research method used in this thesis research is descriptive qualitative method that is by collecting data from research result then analyze it and draw conclusion from research, and research type used is descriptive skin. The results obtained that the accounting system of giving credit home mortgageÂ at PT. Bank Tabungan Negara Branch Officer Manado runs well, and in accordance with the standard set, and is supported by the system E-loan, and Implementation of internal controls in the accounting system of home mortgage loans at PT. Bank Tabungan Negara Branch Officer Manado already meets the internal control elements of COSO well, as it is carried out in accordance with the standard operating policy guidelines of the procedures and policies of the directors.Keywords : Credit, Accounting System, Analysis